Noninvasive Targeted Imaging of Matrix Metalloproteinase Activation in a Murine Model of Postinfarction Remodeling - Haili Su; Francis G. Spinale; Lawrence W. Dobrucki; James Song; Jing Hua; Sarah E. Sweterlitsch; Donald P. Dione; P Cavaliere; Conroy Chow; Brian N. Bourke; Xiao-yu Hu; Michael Azure; et al. (2005)
Background— Time-dependent activation of matrix metalloproteinases (MMPs) after myocardial infarction (MI) contributes to adverse left ventricular (LV) remodeling; however, noninvasive methods to monitor this process serially are needed. Methods and Results— MMP-targeted radiotracers were developed that displayed selective binding kinetics to the active MMP catalytic domain. Initial nonimaging studies were performed with a 111 In-labeled MMP-targeted radiotracer ( 111 In-RP782) and negative control compound ( 111 In-RP788) in control mice (Ctrl) and in mice 1 week after surgically induced MI. Localization of 111 In-RP782 was demonstrated within the MI by microautoradiography. A 334±44% increase ( P <0.001 versus Ctrl) in relative retention of 111 In-RP782 was confirmed by gamma well counting of myocardium. Subsequent high-resolution dual-isotope planar and hybrid micro–single-photon emission computed tomography/CT imaging studies with an analogous 99m Tc-labeled MMP-targeted radiotracer ( 99m Tc-RP805) and 201 Tl demonstrated favorable biodistribution and clearance kinetics of 99m Tc-RP805 for in vivo cardiac imaging, with robust retention 1 to 3 weeks after MI in regions of decreased 201 Tl perfusion. Gamma well counting yielded a similar ≈300% increase in relative myocardial retention of 99m Tc-RP805 in MI regions (Ctrl, 102±9%; 1 week, 351±77%; 2 weeks, 291±45%; 3 weeks, 292±41%; P <0.05 versus Ctrl). Myocardial uptake in the MI region was also significantly increased ≈5-fold when expressed as percentage injected dose per gram tissue. There was also a significant 2-fold increase in myocardial activity in remote regions relative to control mice, suggesting activation of MMPs in regions remote from the MI. Conclusions— This novel noninvasive targeted MMP radiotracer imaging approach holds significant diagnostic potential for in vivo localization of MMP activation and tracking of MMP-mediated post-MI remodeling.